Hemophagocytic lymphohistiocytosis with leukoencephalopathy in a patient with dermatomyositis accompanied with peripheral T-cell lymphoma: a case report. (December 2016) - Teshigawara, Satoru; Katada, Yoshinori; Maeda, Yuichi; Yoshimura, Maiko; Kudo-Tanaka, Eriko; Tsuji, Soichiro; Harada, Yoshinori; Matsushita, Masato; Ohshima, Shiro; Watanabe, Kotaro; Kumode, Takahiro; Hoshida, Yoshihiko; et al.
Abstract Background Hemophagocytic lymphohistiocytosis associated with autoimmune diseases is seen in patients with systemic juvenile idiopathic arthritis, adult-onset Still's disease, and systemic lupus erythematosus, whereas it is rarely seen in patients with dermatomyositis. In addition, central nervous system involvement with dermatomyositis is rare. To the best of our knowledge, this is the first case of hemophagocytic lymphohistiocytosis complicated by leukoencephalopathy in a patient with dermatomyositis accompanied with peripheral T-cell lymphoma. Case presentation A 17-year-old Asian male adolescent with dermatomyositis and hemophagocytic lymphohistiocytosis that were controlled with corticosteroid therapy presented to our hospital with high fever and altered consciousness. Brain magnetic resonance imaging revealed multiple cerebral lesions. We diagnosed the central nervous system lesions as leukoencephalopathy secondary to dermatomyositis and hemophagocytic lymphohistiocytosis. Because corticosteroid and cyclophosphamide pulse therapy was ineffective, he was treated with a modified hemophagocytic lymphohistiocytosis-2004 protocol, which resulted in the disappearance of the lesions of his central nervous system. Conclusions Our findings suggest that the hemophagocytic lymphohistiocytosis-2004 protocol including etoposide should be initiated immediately in patients with hemophagocytic lymphohistiocytosis who respond poorly to treatment for the underlying disease. Moreover, irrespective of the underlying disease, patients with hemophagocytic lymphohistiocytosis with central nervous system lesions might require bone marrow transplantation.